Free Opioid Anesthesia in Cancer Patient Undergoing Total Thyroidectomy and Functional Neck Dissection Dextra: A Case Report - I Putu Eka Ariyasa; Tjokorda Gde Agung Senapathi; Tjahya Aryasa E.M. (HM Publisher, 2023)
Background: The use of large doses of opioids perioperatively has been found to be associated with early recurrence in patients undergoing surgery for primary cancer. This study aimed to describe the use of opioid free anesthesia in cancer patients. Case presentation: A 72-year-old man with a diagnosis of papillary adenocarcinoma thyroid underwent total thyroidectomy and dextra functional neck dissection. The results of the preoperative assessment stated that the patient had ASA III physical status and would undergo general anesthesia (GA-OTT) and regional anesthesia peripheral nerve block (RA-PNB BPSS). Conclusion: Nonopioid regimens are recommended for pain control in the perioperative and postoperative periods in some cases. The application of free opioids can reduce opioid dependence in patients who routinely receive opioid prescriptions after discharge.